Systems biology and metabolic modelling unveils limitations to polyhydroxybutyrate accumulation in sugarcane leaves; lessons for C4 engineering. Issue 2 (25th May 2015) - McQualter, Richard B.; Bellasio, Chandra; Gebbie, Leigh K.; Petrasovits, Lars A.; Palfreyman, Robin W.; Hodson, Mark P.; Plan, Manuel R.; Blackman, Deborah M.; Brumbley, Stevens M.; Nielsen, Lars K.
Summary: In planta production of the bioplastic polyhydroxybutyrate (PHB) is one important way in which plant biotechnology can address environmental problems and emerging issues related to peak oil. However, high biomass C4 plants such as maize, switch grass and sugarcane develop adverse phenotypes including stunting, chlorosis and reduced biomass as PHB levels in leaves increase. In this study, we explore limitations to PHB accumulation in sugarcane chloroplasts using a systems biology approach, coupled with a metabolic model of C4 photosynthesis. Decreased assimilation was evident in high PHB‐producing sugarcane plants, which also showed a dramatic decrease in sucrose and starch content of leaves. A subtle decrease in the C/N ratio was found which was not associated with a decrease in total protein content. An increase in amino acids used for nitrogen recapture was also observed. Based on the accumulation of substrates of ATP‐dependent reactions, we hypothesized ATP starvation in bundle sheath chloroplasts. This was supported by mRNA differential expression patterns. The disruption in ATP supply in bundle sheath cells appears to be linked to the physical presence of the PHB polymer which may disrupt photosynthesis by scattering photosynthetically active radiation and/or physically disrupting thylakoid membranes.